Aerogels as alternatives for thermal insulation in buildings – A comparative teeny review. (2022) - Balaji, D.; Sivalingam, S.; Bhuvaneswari, V.; Amarnath, V.; Adithya, J.; Balavignesh, V.; Ganesh surya, R.
Abstract: Building insulations are the order of the day which paves way for energy saving, cost saving and enhanced comfort. Current day insulation materials are of high cost per unit area albeit better characteristics. This shoots the overall construction cost of any buildings. Aerogels are ultrathin materials derived from various material gels and was proven to possess better insulation behaviour. When it comes to increasing a building's insulating capacity without increasing the cost or influence on the ecosystem, aerogels stand out as the most encouraging substance. Aerogels, on the other hand, proved to be far superior to synthetic insulation substances in a number of studies. Using aerogels has only one remaining challenge: production costs, where they are expected to decline in the near years ahead. A review deems necessary to consolidate the capability of an aerogel as an alternative building insulation material. This review focusses on the general properties of an aerogel, their insulation capabilities in different forms and comparison with conventionally used synthetic aerogels.